Job satisfaction in sport science and sports medicine, an international cross-sectional survey - Gert Ulrich; Anthony Paul Breitbach (BMJ Open Sport & Exercise Medicine, 2023)
Background/Aim Job satisfaction (JS) and professional burnout among health professionals have been shown to affect several factors: healthcare quality, patient safety, patient satisfaction, turnover/reduction of work effort, healthcare costs and other personal consequences. In general, factors that impact JS for health professionals include professional autonomy, workplace conditions, rewards/recognition, compensation and work–life balance. However, less is known about JS of professions working in sport science and sports medicine (SSSM) especially from an international perspective. This paper addresses JS among SSSM professionals in an international context.Methods In a cross-sectional study design, the Interprofessional Collaboration (IPC) in SSSM survey, an online survey which included the Warr-Cook-Wall JS questionnaire for international respondents working in fields associated with SSSM, was distributed globally to persons working in SSSM. Data from 320 respondents with complete data sets from USA (n=83), Canada (n=179) and Europe (n=58) were collected.Results High values were detected in the overall JS of the total sample with some differences in variables relevant for JS internationally and a relationship between positive perceptions of IPC and overall JS. The most important determinant for overall JS in professionals working in SSSM is the opportunity to use abilities.Conclusion JS has an important influence on the work and services provided by SSSM professionals and experience with IPC can have a positive effect on JS which, in turn, can improve quality of life for clients, patients and professionals. Employers should regard most impactful determinants of overall JS when designing working conditions for their employees.